IMPACTS OF OBSTETRIC IMMUNIZATION AGAINST RESPIRATORY SYNCYTIAL VIRUS (RSV) IN CHILDREN: AN INTEGRATIVE REVIEW (REMUNOM, 2025)
Respiratory syncytial virus is the main causative agent of respiratory tract infections, and children up to 5 years of age are among the most affected. This study aims to evaluate the impacts of obstetric immunization against RSV on children of mothers who received the vaccine in question. This study consists of an Integrative Literature Review. During the data collection stage in electronic media, 48 articles were pre-selected, of which 34 were available in PubMed, 13 in BVS and 1 in SciELO. However, after reading the articles, 17 articles were selected. Thus, vaccines against RSV have good efficacy, especially when administered between 32 and 36 weeks of gestation, ranging from 39.4% to 100%, reducing the number of hospitalizations due to respiratory infections in newborns, decreasing mortality and increasing prevention of RSV. Regarding safety, the vaccines are safe and well tolerated, but some adverse effects have been documented, including premature birth, uterine growth restriction, and low birth weight. Therefore, this study found that these obstetric vaccinations were effective against respiratory syncytial virus infection, reducing the severity and, consequently, morbidity and mortality in the affected pediatric population, when administered mainly between the 32nd and 36th weeks of gestation. In addition, this immunization was safe in most of the populations involved; however, some adverse effects were reported, such as preeclampsia, premature birth, and low birth weight. Therefore, further research on these immunizations is recommended.